2013
DOI: 10.1684/mrh.2013.0332
|View full text |Cite
|
Sign up to set email alerts
|

Platelet serotonin and magnesium concentrations in suicidal and non-suicidal depressed patients

Abstract: The pathophysiology and treatment of depression involves monoamine neurotransmitters and the magnesium (Mg)-modulated monoaminergic pathway. Serum and platelet Mg concentrations and platelet serotonin concentrations were measured in 79 depressed patients who had attempted suicide, and 101 patients without suicidal behaviour, according to the ICD-10 diagnoses F 33.2 and F32.2, with or without intentional self-harm (X60-X84). The control group consisted of 77 voluntary blood donors. The platelet serotonin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…Thus, the group rarely consuming magnesium food sources was more at risk of experiencing emotional eating. Previous study revealed that magnesium intake has an effect on serotonin levels in the blood of depressed patients (23). Serotonin is a hormone synthesized by the central nervous system and cells in the digestive tract and plays an important role in depression, appetite control, and also stress control mechanism (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the group rarely consuming magnesium food sources was more at risk of experiencing emotional eating. Previous study revealed that magnesium intake has an effect on serotonin levels in the blood of depressed patients (23). Serotonin is a hormone synthesized by the central nervous system and cells in the digestive tract and plays an important role in depression, appetite control, and also stress control mechanism (10).…”
Section: Resultsmentioning
confidence: 99%
“…Stress level data were collected through Depression Anxiety Stress Scales (DASS 42) questionnaire with the following categories: normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26-33) and very severe (> 34) [14]. Physical activity data were gathered through International Physical Activity Questionnaire (IPAQ) with the following categories: vigorous activity (>3000 METs/week), moderate activity (600-3000 METs/week) and light activity (<600 METs/week) [15].…”
Section: Methodsmentioning
confidence: 99%
“…Having depressive symptoms is an important risk factor for suicide, not only in patients with MDD but with various diagnoses like schizophrenia or alcohol dependence [2,28,29]. This is interesting, as there is some evidence for the relationship between lower albumin levels and attempted suicide [30], which is an important risk group for completed suicide [2][3][4]. These findings, taken together with the well-replicated negative association between depressive symptoms and albumin [10,[12][13][14][15][16][17][18][19][20][21][22][23], raise the issue whether there may be an association between albumin and depressive symptoms among individuals with a recent suicide attempt.…”
Section: Introductionmentioning
confidence: 98%
“…The exclusion of individuals with a history of attempted suicide or with current suicidality may account for the plasma magnesium concentrations observed. Ruljancic et al [15] found lower serum magnesium concentrations in MDD patients who had attempted suicide as compared to MDD patients who had not, and controls. Thus, hypomagnesaemia in MDD impacting some specific psychopathological features might be a secondary phenomenon corresponding to exposure to antidepressants, drug-resistance, medical comorbidity, suicidality, impulsivity, pronounced anxiety, or the chronic course of the disorder linked to a persistent proinflammatory response [1][2][3][4][5]15].…”
Section: Staix-1 Staix-2mentioning
confidence: 99%